2015
DOI: 10.1186/s12958-015-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different methods for measuring anti-mullerian hormone in a clinical series

Abstract: BackgroundAnti Mullerian hormone (AMH) has previously been measured using a manual method, but a fully automated assay from Roche Diagnostics was recently introduced. The aim of this study was to compare the results from the AMH gen II ELISA and Elecsys Cobas AMH methods in a clinical setting to evaluate whether the assays achieve the goals of analytical performance.A prospective observational study with 23 women seeking laparoscopic sterilization was conducted. Blood samples were collected preoperatively as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…However, since 2014, Elecsys Cobas (Roche), a new automated assay, was proven as a better method for measuring AMH . In our study, AMH was determined by an Elecsys Roche System based on the ECLIA technology, which was a fully automated assay and approved to be the optimal standard for biochemical assays …”
Section: Discussionmentioning
confidence: 99%
“…However, since 2014, Elecsys Cobas (Roche), a new automated assay, was proven as a better method for measuring AMH . In our study, AMH was determined by an Elecsys Roche System based on the ECLIA technology, which was a fully automated assay and approved to be the optimal standard for biochemical assays …”
Section: Discussionmentioning
confidence: 99%
“…The main strength of the current study is the within-patient comparisons of changes in ovarian reserve markers. Another strength is the use of the fully automated Elecsys AMH Plus assay, which shows significantly lower betweenand intra-assay variability than previously used assays (Anckaert et al, 2016;Hyldgaard et al, 2015;Rustamov et al, 2014). It has been debated whether AMH concentrations vary significantly intra-and inter-cyclically; however, most studies agree that there is no clinically relevant intra-cyclic variation and even less inter-cyclic variation (La Marca et al, 2013;Lambert-Messerlian et al, 2016;Rustamov et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…AMH concentrations were analysed using the fully automated Elecsys AMH Plus assay (Roche Diagnostics, Germany) with low reported coefficients of variation of ≤4.4% for intermediate precision and ≤1.8% for repeatability based on a multicentre study (Anckaert et al, 2016). This is a more sensitive assay (limit of quantification 0.21 pmol/l) with a lower between-and intra-assay variability compared with previous assays (Cohen and Adams, 2011;Hyldgaard et al, 2015;Van Helden and Weiskirchen, 2015). FSH, LH and oestradiol were likewise analysed using Elecsys assays.…”
Section: Hormonal Analyses Of Blood Samplesmentioning
confidence: 99%
“…In support of our results, van Helden and Weiskirchen [22] demonstrated good correlations between the Gen II ELISA and both the Access AMH assay and the new automated Elecsys system from Roche, both of which utilise the same monoclonal antibodies. The authors also demonstrated an extremely tight correlation between the Access and Elecsys assays, and these results were further [28] demonstrated a similar pattern of bias between the Gen II and Elecsys methods and proposed that this may be in part due to inter-laboratory bias with the Gen II method. The Gen II ELISA is a manual method and thus would be more prone to inter-operator bias and variation from a number of sources within the assay itself.…”
Section: Discussionmentioning
confidence: 74%